Suppression of pain‐related behavior in two distinct rodent models of peripheral neuropathy by a homopolyarginine‐conjugated CRMP2 peptide. (20th January 2013) - Ju, Weina; Li, Qi; Allette, Yohance M.; Ripsch, Matthew S.; White, Fletcher A.; Khanna, Rajesh
Abstract The N‐type voltage‐gated calcium channel (CaV2.2) is a clinically endorsed target in chronic pain treatments. As directly targeting the channel can lead to multiple adverse side effects, targeting modulators of CaV2.2 may prove better. We previously identified ST1‐104, a short peptide from the collapsin response mediator protein 2 (CRMP2), which disrupted the CaV2.2–CRMP2 interaction and suppressed a model of HIV‐related neuropathy induced by anti‐retroviral therapy but not traumatic neuropathy. Here, we report ST2‐104 –a peptide wherein the cell‐penetrating TAT motif has been supplanted with a homopolyarginine motif, which dose‐dependently inhibits the CaV2.2–CRMP2 interaction and inhibits depolarization‐evoked Ca2+ influx in sensory neurons. Ca2+ influx via activation of vanilloid receptors is not affected by either peptide. Systemic administration of ST2‐104 does not affect thermal or tactile nociceptive behavioral changes. Importantly, ST2‐104 transiently reduces persistent mechanical hypersensitivity induced by systemic administration of the anti‐retroviral drug 2′, 3′‐dideoxycytidine (ddC) and following tibial nerve injury (TNI). Possible mechanistic explanations for the broader efficacy of ST2‐104 are discussed.